PSYCHOLOGICAL AND TEACHING METHODS OF TRAINING STUDENTS FOR THE PREVENTION OF TEENAGERS’ VICTIMIZING BEHAVIOR - Bocheliuk, Vlada (Psychological Prospects Journal, 2014)
Bocheliuk V. V. Psychological and Teaching Methods of Training Students for the Prevention of Teenagers’ Victimizing Behavior. The article defines psycho-pedagogical conditions of preparing psychology students for the preventiion of teen’s victimizing behavior. The author points out that psychological and pedagogical conditions for training future psychologists at higher education institutions are regarded as interdependent elements of the academic process, as  the factors that are believed by teachers and students to affect the state of each of them, to encourage them to enhancetheir own activities to develop professional competence of future psychologists. The author argues that professional motivation as a process of students’ value orientation, organization of self-education and learning of students, ensuring the formation of professional identity of future psychologists by means of interactive technologies are viewed as basic psycho-pedagogical conditions. The students’ subjectivity, his self-awareness, self-reliance, initiative, self-development in the process of self-education are treated as the main factors of future psychologists’ professional training. The effectiveness of self-education serves as an indicator of forming their cognitive component in the profession. A special attention in the paper is paid to the professional identification of future psychologists. Thus the students who acquire professional skills in simulated situations are able to identify the interest and understanding of their own professional competence and acceptance of one’s ‘self’ as an effective expert, realizing his future profession opportunities, analyzing the prototype of profession, projecting the image of the professional future, thinking about his own profession. The research results proved the efficiency of introducing a set of workshops, aiming at the organization of preventing work with victimizing teenagers, into the academic process of bachelors specialized in psychology.Keywords: victimizing behavior, teenagers, training, future psychologist, conditions.